2013
DOI: 10.5194/amt-6-2207-2013
|View full text |Cite
|
Sign up to set email alerts
|

Measurements on pointing error and field of view of Cimel-318 Sun photometers in the scope of AERONET

Abstract: Abstract. Sensitivity studies indicate that among the diverse error sources of ground-based sky radiometer observations, the pointing error plays an important role in the correct retrieval of aerosol properties. The accurate pointing is specially critical for the characterization of desert dust aerosol. The present work relies on the analysis of two new measurement procedures (cross and matrix) specifically designed for the evaluation of the pointing error in the standard instrument of the Aerosol Robotic Netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…The first tests on this topic, done with seven photometers in the work by Torres et al (2013), showed that for most of the instruments the magnitudes of ξ θ and sin θ s ξ ϕ were smaller than 0.1 • . The maximum values obtained for vertical and horizontal error were 0.25 • , while the maximum of the total error, ξ , was 0.3 • .…”
Section: Dependence On the Pointing Errormentioning
confidence: 99%
See 2 more Smart Citations
“…The first tests on this topic, done with seven photometers in the work by Torres et al (2013), showed that for most of the instruments the magnitudes of ξ θ and sin θ s ξ ϕ were smaller than 0.1 • . The maximum values obtained for vertical and horizontal error were 0.25 • , while the maximum of the total error, ξ , was 0.3 • .…”
Section: Dependence On the Pointing Errormentioning
confidence: 99%
“…The work by Torres et al (2013) (also in Torres, 2012) describes a methodology used for the characterization of these magnitudes and a first evaluation of the results for several individual instruments (all of them Cimel 318 sun photometers). One of the main outcomes of this evaluation is that the magnitudes ξ θ and sin θ s ξ ϕ are constant for each photometer, regardless of θ s .…”
Section: Dependence On the Pointing Errormentioning
confidence: 99%
See 1 more Smart Citation
“…We follow the retrieval strategy introduced in Wagner et al (2009a) and apply the DOAS settings from Wagner et al (2009b) to retrieve the RSP in the fitting window of 426-440 nm. The only atmospheric cross section absorber adjusted to the spectrometer resolution that is included in the analysis is NO 2 (Vandaele et al, 1998). A thirdorder polynomial is fitted to account for broad band spectral structures.…”
Section: Doas Retrieval Of Differential Rsp and Intensitiesmentioning
confidence: 99%
“…After matching the measurements, 1067 AERONET and SAM profiles remained. The measurements with the same ξ to the east and west directions of the Sun were averaged to minimize the effects of small pointing errors (Torres et al, 2013). Ideally for these 1067 profiles there should be 5335 measurements of radiance corresponding to the five values from AERONET for ξ < 6 • , where the maximum ξ from the AERONET measurements was found to be 5.8 • .…”
Section: Cross-comparison Between Aeronet and Sam Datamentioning
confidence: 99%